Strengthening the Competency of the Casemix Team to Improve the Quality of Outpatient Services at Grandmed Hospital - Anggi Kurnia Ningsih (JURNAL PENGMAS KESTRA (JPK), 2026)
The Casemix Team plays a strategic role in supporting healthcare claim management, diagnosis and procedure coding, and providing accurate data to improve hospital service quality. However, various challenges remain, including limited knowledge and technical skills among personnel in diagnosis coding, medical record verification, and healthcare claim management, which may reduce service efficiency and delay the National Health Insurance (JKN) claim process. This Community Service Program aimed to strengthen the competencies of the Casemix Team in improving the quality of outpatient services at Grandmed Hospital. The program was implemented through educational sessions, training, mentoring, case-based simulations, and evaluations using pre-test and post-test assessments. A total of 25 participants, consisting of Casemix team members, coding officers, claim verifiers, medical record staff, and administrative personnel involved in Casemix management, participated in the program. The training covered Casemix concepts, diagnosis and procedure coding based on ICD and INA-CBG's standards, medical record verification, and healthcare claim management. The evaluation results demonstrated a significant improvement in participants' competencies, with the average score increasing from 61.4 in the pre-test to 85.7 in the post-test, representing an improvement of 39.6%. Participants also showed better performance in accurate diagnosis and procedure coding, document verification, and claim management. Overall, this community service program effectively strengthened the competencies of the Casemix Team and contributed to improving outpatient service quality, administrative efficiency, and healthcare claim management at Grandmed Hospital.